Pathogen-induced hijacking of host SUMOylation: from molecular mechanisms and prospects for therapeutic modulation - Padmakumar, Sandhya; Madhavan, Aravind; Nair, Bipin G.; Kumar, Geetha B. (Frontiers in Immunology, 2025)
Post-translational modifications (PTMs) serve as essential regulatory mechanisms that fine-tune protein function, stability, localization, and interaction networks, enabling cells to adapt rapidly to physiological and pathological cues. Among the diverse PTMs, SUMOylation—the covalent attachment of Small Ubiquitin-like Modifier (SUMO) proteins to specific lysine residues on target substrates—has emerged as a dynamic and reversible modification with far-reaching implications in cellular homeostasis. Beyond its well-established roles in transcriptional regulation, DNA repair, and stress responses, recent studies highlight how pathogens have evolved to hijack the host SUMOylation machinery to subvert immune signalling, dampen inflammatory responses, and enhance intracellular survival. This review delves into the multifaceted role of SUMOylation in infectious disease, emphasizing its interplay with key host signalling cascades/axes such as NF-κB, MAPK, JAK-STAT, and interferon pathways. We explore how bacterial, viral, and fungal pathogens manipulate SUMOylation to reprogram host chromatin, modulate vesicular trafficking, and evade cytokine-mediated defences. Additionally, we examine the crosstalk between SUMOylation and other PTMs—such as ubiquitination, phosphorylation, and acetylation—that collectively shape the host-pathogen interface. By synthesizing current evidence on pathogen-driven SUMO modulation, we offer an integrated view of how this modification governs immune outcomes. Lastly, we evaluate emerging therapeutic strategies aimed at targeting SUMOylation pathways through small molecule inhibitors and genetic tools, with the goal of restoring immune competence and mitigating persistent infections. These insights position SUMOylation as a critical regulatory node and a promising target for host-directed therapies against infectious diseases.